Preventive and curative effect of the methanolic extract of Ajuga iva on collagen induced arthritis in rats - Lekhmici, Arrar; Abdelwahab, Diafet; Noureddine, Charef; Seddik, Khennouf; Abderrahmane, Baghiani (Pharmacognosy Communications)
Introduction: The medicinal plants are widely used around the world. Rheumatoid arthritis (RA) affects 1% of the adult population, and has a significant impact on physical functioning and social life. In rats, induction of arthritis by collagen II causes alterations of synovial joints similar to patients with RA. In this study the collagen induced arthritis model was used to evaluate the anti-arthritic effect of Ajuga iva extract. Materials and Methods: Arthritis was induced by collagen emulsified with complete Freund’s adjuvant. Arthritic rats were treated orally with the methanolic extract of Ajuga iva. To study the preventive effect, 30 and 60 mg/kg of body weight, were daily administrated during the first 21 days. For the curative effect, 100 and 150 mg/kg of body weight were daily administrated during 21 days starting from the appearance of arthritis signs. Changes in body weight, swelling of legs, level of protein C, sedimentation rate, and the histopathological status of articulation were evaluated as markers of inflammation associated with arthritis. Results: In the preventive treatment of rats, the methanolic extract of A. Iva inhibited significantly the markers of inflammation and arthritis. Ajuga iva extract, in the curative treatment study, reduced significantly the swelling of legs and other parameters of inflammation such as C reactive protein (CRP) level, erythrocyte sedimentation rate (ESR) and leukocytes. Histopathological examination showed reduced erosion and destruction of bone. Conclusion: Our results show that the methanolic extract of A. iva plays an effective role in the prevention and treatment of collagen inducedarthritis. The way by which the components contained in this extract act to prevent or to reduce the inflammation is not clear but it may be due to their inhibition of the pro-inflammatory cytokines.
Keywords: Ajuga iva; methanolic extracts; collagen induced arthritis; anti-arthritic effects; joint inflammation